A comparative analysis of ACE Inhibitors and ARBs as cancer risk factors - Belle Tamir Brahms; Shani Afek; Michael Hopp; Martine Granek-Catarivas; Yair Levy; Tzipi Hornik-Lurie (PLoS ONE, 2026)
Importance Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are widely prescribed antihypertensive agents. Although their cardiovascular and renal benefits are well established, uncertainty remains regarding their long-term associations with cancer risk. Objective To compare cancer incidence among patients treated exclusively with ACEIs or ARBs in a large population-based cohort with long-term follow-up. Design, setting, and participants Retrospective cohort study using electronic health records from Clalit Health Services, Israel’s largest healthcare organization. The source population included hypertensive adults aged 40 years or older who were free of cancer on January 1, 2000 (n = 1,048,575). After applying eligibility criteria and excluding patients who switched between treatment groups or were non-compliant with therapy, the final analytic cohort included 346,405 exclusive ACEI users and 77,018 exclusive ARB users. Exposure Exclusive treatment with either ACEIs or ARBs. Cancer incidence analyses were conducted during an active follow-up period from 2002 through 2024, allowing for a two-year exposure window. Main outcomes and measures The primary outcome was diagnosis of any cancer. Secondary outcomes included the ten most prevalent cancer types diagnosed during follow-up. Cancer incidence rates, odds ratios (ORs), age at diagnosis, and time from treatment initiation to cancer diagnosis were compared between treatment groups after adjustment for age, sex, and exposure duration. Results During follow-up, overall cancer incidence differed between treatment groups. ACEI therapy was associated with lower overall odds of cancer than ARB therapy. Associations varied across specific cancer types, with lower odds observed among ACEI users for several common malignancies, whereas no meaningful difference was observed for leukemia. Differences in age at diagnosis and time to diagnosis were also observed between treatment groups. Conclusions and relevance In this large population-based cohort, long-term cancer risk differed between patients treated exclusively with ACEIs and those treated exclusively with ARBs. While the observational design precludes causal inference, the findings contribute to the ongoing evaluation of the long-term oncologic safety profiles of RAAS-modulating therapies. Further prospective and mechanistic studies are needed to clarify the biological basis and clinical significance of these associations.